Effects of electrostatic therapy on nighttime sleep and daytime symptoms in patients with chronic insomnia: Evidences from an open label study - Dai, Yanyuan; Qin, Qingsong; Chen, Baixin; Chen, Le; Sun, Qimeng; Vgontzas, Alexandros N.; Basta, Maria; Li, Yun (Frontiers in Neuroscience, 2023)
Introduction Transcranial electric stimulation (TES) is a neuromodulation approach that applies low-intensity electrical current to the brain and has been proposed as a treatment for insomnia. Electrostatic therapy is a kind of TES and people do not have a feeling of electrical stimuli when the voltage of static electricity is lower than 2,000 volts. However, no studies have examined the effects of electrostatic therapy on objective sleep and daytime symptoms in patients with insomnia. Materials and methods Thirty chronic insomnia patients were included. All patients received a 6 week electrostatic therapy and three comprehensive assessments including two consecutive polysomnography (PSG) and daytime symptoms assessments, at pre-treatment, 3 week and 6 week of treatment. Insomnia Severity Index (ISI) was used to assess the severity of insomnia. Multiple sleep latency test (MSLT), Epworth Sleepiness Scale (ESS), and Flinders Fatigue Scale (FFS) were used to assess objective and self-reported daytime sleepiness and fatigue, respectively. Attention network test (ANT) was used to assess attention levels. Results Total ISI scores decreased significantly at 3 weeks (p < 0.001) and 6 weeks (p < 0.001) after initiation of treatment. Furthermore, objective total sleep time (TST, p = 0.020) and sleep efficiency (SE, p = 0.009) increased and wake time after sleep onset (p = 0.012) decreased significantly after 6 weeks electrostatic therapy. Regarding daytime symptoms, ESS and FFS scores decreased significantly at 3 weeks (ESS, p = 0.047; FFS, p = 0.017) and 6 weeks (ESS, p = 0.008; FFS, p = 0.003) after initiation of treatment. Moreover, executive control improved significantly from pre-treatment to 3 weeks (p = 0.006) and 6 weeks (p = 0.013) and altering network improved significantly at 6 weeks (p = 0.003) after initiation of treatment. Secondary analyses showed that TST and SE improved significantly after electrostatic therapy in insomnia patients who slept < 390 min (all p-value < 0.05). However, no significant changes regarding TST and SE were observed in insomnia patients who slept ≥ 390 min. Conclusion Electrostatic therapy improves both nighttime sleep and daytime symptoms in patients with chronic insomnia. The effect on objective sleep appears to be stronger in patient with objective short sleep duration. Electrostatic therapy might be a therapeutic choice for insomnia patients with difficulty maintaining sleep and not responding to behavioral treatments. Clinical trial registration [www.clinicaltrials.gov], identifier [ChiCTR2100051590].